Strong as a Hippo’s Heart: Biomechanical Hippo Signaling During Zebrafish Cardiac Development - Bornhorst, Dorothee; Abdelilah-Seyfried, Salim (Frontiers in Cell and Developmental Biology, 2021)
The heart is comprised of multiple tissues that contribute to its physiological functions. During development, the growth of myocardium and endocardium is coupled and morphogenetic processes within these separate tissue layers are integrated. Here, we discuss the roles of mechanosensitive Hippo signaling in growth and morphogenesis of the zebrafish heart. Hippo signaling is involved in defining numbers of cardiac progenitor cells derived from the secondary heart field, in restricting the growth of the epicardium, and in guiding trabeculation and outflow tract formation. Recent work also shows that myocardial chamber dimensions serve as a blueprint for Hippo signaling-dependent growth of the endocardium. Evidently, Hippo pathway components act at the crossroads of various signaling pathways involved in embryonic zebrafish heart development. Elucidating how biomechanical Hippo signaling guides heart morphogenesis has direct implications for our understanding of cardiac physiology and pathophysiology.